Chimeric antigen receptor (CAR) T-cell treatment for mantle cell lymphoma (MCL). (February 2022) - Tbakhi, Bushra; Reagan, Patrick M.
Mantle cell lymphoma (MCL) is a rare B-cell malignancy that remains challenging to treat with high rates of relapse. Frontline strategies range from intensive chemotherapy followed by consolidation with autologous stem cell transplant (ASCT), to less-intensive therapies including combination regimens. The treatment landscape for relapsed patients includes Bruton tyrosine kinase (BTK) inhibitors among other targeted treatments. Novel agents such as the selective BCL2 inhibitor venetoclax showed high response rates when used as monotherapy for refractory relapsed MCL. The rituximab, bendamustine, and cytarabine (R-BAC) regimen, while response rates were high, were not durable. Chimeric antigen receptor (CAR) T-cell products targeting CD19 have been efficacious in relapsed and refractory MCL patients. Brexucabtagene autoleucel (brexu-cel, formerly KTE-X19) was approved by US Food and Drug Administration (FDA) in July, 2020, for treatment of refractory and relapsed MCL. This article provides an overview for the available management strategies for relapsed MCL and examines the role of CAR T-cell in the current and future treatment of MCL.